The Influence of Conformity, Brand Image and Hedonic Life Style on Consumer Behavior and Consumer Loyalty of Shopee E-Commerce Users in the City of Surabaya - Kusumasari, Indah Respati; Kusuma, Yanda Bara (GoAcademica Research & Publishing, 2025)
The development of increasingly modern times, science and technology (IPTEK) which is increasingly advanced and developing has a big impact or impact on its users. The impact can be seen in changes in people's lifestyles in this era, who tend to be active in the internet world, and information technology provides convenience and wider reach to its users. Currently, the internet is a form of technological development that is a necessity for most people. Technological developments can not only be used as a medium of information, but also make buying and selling transactions easier. The existence of an online shop is another implementation of technology to improve business or a means of buying and selling products through electronic commerce (e-commerce). Indonesia already has many e-commerce sites, including Shopee. This research uses a survey and quantitative research method approach. In accordance with the research objectives, this research approach explorative descriptive, namely research by conducting and providing descriptions of symptoms and phenomena that occur in the field. However, this research is also directed at explaining the influence between variables (explanatory) by carrying out a hypothesis test. The result of this research is conformity has a significant effect on consumer behavior of Shopee E-Commerce users in the city of Surabaya.Brand Images has a significant effect on consumer behavior of Shopee E-Commerce users in the city of Surabaya Hedonic Life Style has a significant effect on consumer behavior of Shopee E-Commerce users in the city of Surabaya conformity has a significant effect on consumer loyalty of Shopee E-Commerce users in the city of Surabaya Hedonic Life Style has a significant effect on consumer loyalty of Shopee E-Commerce users in the city of Surabaya. Consumer behavior has a significant effect on consumer loyalty of Shopee E-Commerce users in the city of Surabaya.